Impacts of child gender on parents' conversational dominance - Crinis, La-Mia (2024)
Prior studies pinpoint that gender stereotypes may be reflected in parent-child conversations whereby more assertive speech is used by men to communicate with women or children. This study investigates if child gender influences parent-child conversational dominance by examining (i) the number of words spoken, (ii) length of turn speaking (expressed as the average number of words per turn), and (iii) wh-questions (e.g., who, what, when) asked by parents. 97 Singaporean parent-child dyads (mean child age: 8.9 years, 49 girls) participated in shared storybook sessions. The picture-book was designed to facilitate parent-child conversation, and contained open and close-ended prompts about the story’s protagonists. Parent-child conversations were transcribed using the Codes for the Human Analysis of Transcripts format. High inter-coded reliability was achieved for the coding of wh-questions (κ = .89). The three aspects of conversational dominance were analysed using Computerized Language Analysis. Length of turns were more balanced in parent-child conversations with girls than with boys, ( . ) = − . , =. , contradicting expectations for girls’ parent-child conversations to be more dominated. This finding may be attributed to the socialisation of girls, who are encouraged to develop their interpersonal sensitivity more than boys (Leaper & Robnett, 2011). However, parents’ word count and wh-question frequency did not differ significantly based on child gender, challenging the predicted gender stereotypes in parent-child conversations. These findings urge for the need of a replicated study to be conducted in a real-world setting to further validate these observations on child gender.